1993
DOI: 10.1121/1.407267
|View full text |Cite
|
Sign up to set email alerts
|

The sounds of bicolor damselfish (Pomacentrus partitus): Predictors of body size and a spectral basis for individual recognition and assessment

Abstract: Evidence is provided that the "chirp," a sound commonly produced by males of the bicolor damselfish (family: Pomacentridae) possesses an anatomical constraint: The peak frequency within its power spectrum reflects a clear inverse relationship to body size. For every 1-mm change in the standard length of a male (range: 50-69 mm), the peak frequency of its sounds shifts by approximately 20 Hz. The ultimate constraint appears to be the volume of an individual's gas bladder. This provides an individualistic featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 19 publications
(23 reference statements)
4
101
0
Order By: Relevance
“…Another consequence of masking could be that sexual signals are still detected, but that specific acoustic cues in the signals that are important for mate selection get lost. In fish, allometric correlations with acoustic features provide ample opportunity for female mate selection that targets male size [47,50,51]. Although no data are available yet on acoustic preferences of female fish for sounds of large males over sounds of small males, the phenomenon has been tested, confirmed and shown to be noise-level dependent in frogs [69,70].…”
Section: Reviewmentioning
confidence: 83%
See 1 more Smart Citation
“…Another consequence of masking could be that sexual signals are still detected, but that specific acoustic cues in the signals that are important for mate selection get lost. In fish, allometric correlations with acoustic features provide ample opportunity for female mate selection that targets male size [47,50,51]. Although no data are available yet on acoustic preferences of female fish for sounds of large males over sounds of small males, the phenomenon has been tested, confirmed and shown to be noise-level dependent in frogs [69,70].…”
Section: Reviewmentioning
confidence: 83%
“…Distinct variation in spectral and temporal characteristics can be related to species [46,47], populations [48], and gender [49]. Furthermore, graded variation in pitch and duration can be correlated with size [47,50,51] or seasonal fluctuations in motivation [52]. Such acoustic variation means that sounds can serve as information carriers in acoustic communication among fish [43,44,53].…”
Section: Masking Of Acoustic Communicationmentioning
confidence: 99%
“…Two hypotheses for the mechanism underlying peak frequency of discrete pulsed sounds in fish with swimbladders are found in the literature. The 'resonance hypothesis' proposes that the peak frequency of pulsed sounds is imparted by the resonance characteristics of the swimbladder causing this feature to be size dependent (Harris 1964;Myrberg et al 1993). More recently, Connaughton et al (2000) and Fine et al (2001) have put forward the 'forced response' hypothesis, which suggests that the dominant frequency of fish pulsed sounds involving a swimbladder results from the forced response of the sonic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The most serious challenge to our thesis comes from a classic paper on the bicolour damselfish in which peak frequency declines markedly with fish size, potentially implicating swimbladder resonance [53]. Subsequent work indicated that damselfish sounds are initiated by a stretched ceratomandibular ligament that causes a rapid mouth closure and collision of front teeth [54].…”
Section: Discussionmentioning
confidence: 99%